The Influence of Work Stress, Incentives, and Motivation on the Performance of Shopeefood Drivers in Cirebon - Yoan Ardiansyah; Nihayatun Nabila; Siti Maryam (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of work stress, incentives, and motivation on the performance of ShopeeFood drivers in Cirebon. A quantitative method with an associative approach was used in this study, with 138 drivers as the sample. Data were collected through questionnaires and analyzed without explicitly displaying statistical results. The results showed that job stress has a negative impact on driver performance, while incentives and motivation have a positive and significant effect. Simultaneously, these three variables contributed 52.1% to driver performance, indicating that these factors are very important in improving their performance. This study has limitations in terms of area coverage and limited sample. Therefore, further research is recommended to examine other factors that can affect driver performance more broadly.